P18 Respiratory viruses lead to airway dysbiosis in exacerbations of chronic obstructive pulmonary disease. (11th November 2022) - Pritchard, R; Wiseman, D; Shahbakti, H; MacLeod, M; Gent, J; Ritchie, A; Donaldson, GC; Finney, LJ; Wedzicha, JA
Abstract : Background: Respiratory viruses are important triggers of chronic obstructive pulmonary disease (COPD) exacerbations. Secondary bacterial outgrowth commonly occurs in exacerbations triggered by rhinovirus infection. However, few studies have investigated whether secondary bacterial infection occurs in exacerbations with other respiratory viruses. Hypothesis: We hypothesised that secondary bacterial infection occurs in several common respiratory viruses and associated with worse symptoms, decreased lung function and increased airway inflammation. Methods: Sputum was obtained from participants of the London COPD cohort between 01/01/2017 and 31/12/2020 REC 09/H0720/8. Respiratory viruses respiratory syncytial virus, rhinovirus, influenza A, influenza B, parainfluenza, human metapneumovirus and community coronaviruses were detected by multiplex PCR. Quantitative PCR analysis was performed for detection of Haemophilus influenzae, Streptococcus pneumoniae and Moraxella catarrhalis. Bacterial load was correlated with symptom data and lung function changes. Results: There were 30 exacerbations with a respiratory virus detected at exacerbation onset. Of these 73% were treated with antibiotics and 63% treated with oral corticosteroids. Bacteria were identified by qPCR in 83% of samples at exacerbation onset The most frequently detected bacterium at exacerbation onset was S. pneumoniae (70%), with H. influenzae and M. catarrhalis both being identified in 43% of sputum samples. At two weeks bacteria were detected by qPCR in 100% of sputum samples. M. catarrhalis was the most prevalent bacterium (100%). S. pneumoniae and H. influenzae were detected in seven (64%) and five (45%) of the two-week samples respectively. There was a significant increase in median bacterial load at two weeks compared to exacerbation onset (p=0.049) There was no relationship between exacerbation severity defined by change in lung function and bacterial load. There was no significant difference in bacterial load at two weeks between patients who received antibiotics or steroids. Conclusions: Secondary bacterial outgrowth occurs in COPD exacerbations caused by a range of respiratory viruses suggesting that viral infection results in microbiome dysbiosis. Bacterial qPCR detected several bacteria that were not identified using standard microbiological culture with a high bacterial load and Moraxella detection at two weeks Bacterial overgrowth may explain why some exacerbations show prolonged recovery.